Anti-disturbance anti-cracking concrete and preparation method thereof
Through the modified aggregate and fiber cross-over overlap technology, the problems of easy separation and cracking of concrete aggregates under vibration conditions are solved, and the uniform distribution of concrete in vibrating environments is achieved and the high-strength crack resistance of concrete is achieved.
Patent Information
- Application Number
- CN202411714757.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
Under the condition of structural disturbance caused by the inability to interrupt traffic and reduce traffic loads, the aggregate is prone to segregation in the flowing state, and is prone to cracking and strength decreases during the condensation and hardening process.
By promoting the suspension of the modified aggregate and thickening of the cement-based slurry, the fibers are cross-over and blocked by using modified iron tailings sintered aggregates to maintain the vertical and vertical distribution of the fibers under vibration conditions, and achieve vibration reduction, toughening, crack resistance, and vibration resistance Effect.
Under vibration conditions, the aggregate distribution of modified concrete is more uniform, avoiding the layered separation of cement and aggregate, improving the compressive strength and crack resistance of concrete, and reducing the generation and development of cracks.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to an anti-disturbance and anti-cracking concrete and a preparation method thereof. Background Art
[0002] As an important infrastructure of modern transportation, bridges play a vital role in the development of the transportation industry. In recent years, with the rapid development of the economy, the demand for transportation has increased day by day. In addition, due to the frequent occurrence of overweight vehicle loads, a large number of cement concrete highway bridges need to be widened or repaired and reinforced. If the traffic is closed for a long time during the construction process, it will increase the detour distance of vehicles, bring many traffic disadvantages, and have a great social impact. In addition, some projects cannot achieve traffic closure. Therefore, under normal circumstances, the widening or repair and reinforcement of concrete highway bridges are mostly constructed in the way of normal traffic or half-width traffic, which causes the fresh concrete to be continuously affected by the vehicle-bridge coupling vibration during the construction and coagulation and hardening process. Appropriate vibration helps to release the bubbles inside the concrete, reduce the viscosity inside the concrete, and make the concrete completely fill the formwork, but continuous excessive vibration has a more serious adverse effect on the performance and internal structure of the concrete.
[0003] Continuous high-frequency vibration of the axle structure will aggravate the early segregation of concrete. The negative impact on fresh concrete in a flowing state is mainly manifested in the floating of cement paste and the sinking of coarse aggregate. The floating of the paste leads to an increase in the water-cement ratio of the concrete surface, a decrease in the internal water-cement ratio, and uneven concrete density. The sinking of aggregates leads to changes in the internal skeleton structure of the concrete, an increase in porosity, and deterioration of the internal structure. In addition, the initial setting to final setting stage is the stage where cement hydration products are formed the fastest and the stage where strength increases rapidly. Continuous structural disturbances in this stage will destroy the structure of cement hydration products, reduce the strength of concrete, form cracks on the surface, and significantly deteriorate the durability of the structure.
[0004] The disturbance-resistant concrete prepared by the prior art mainly reduces the setting time of concrete and shortens the disturbance period of concrete by adding early strength agents or setting regulating admixtures. However, the large-scale use of early strength agents will lead to a rapid increase in the early strength of concrete, but the later strength development will be limited. At the same time, it will cause higher shrinkage stress in the concrete during the hardening process, increase the risk of cracking, and especially under vibration conditions, the crack resistance of concrete will be greatly weakened. In terms of improving crack resistance, most of them are achieved by adding anti-cracking materials such as fibers or expansion agents. Fibers can reduce the tensile stress inside the concrete and reduce cracks under static conditions, but under dynamic conditions of continuous high-frequency vibration, the fibers in the cement paste are easily changed from the original criss-cross distribution to a relatively consistent distribution in direction. At the same time, it is difficult for fibers to absorb or weaken the vibration energy transmitted from the outside to the inside of the concrete, and the anti-cracking effect is significantly reduced. Chinese Patent 202311756345.5 provides a disturbance-resistant concrete and a preparation method thereof. The concrete formula materials mainly use polycarboxylic acid water-reducing agent, different mineral admixtures, an disturbance-resistant agent composed of early strength agent, retarder, defoaming agent components, and steel fiber. This solution mainly improves the disturbance resistance of concrete by utilizing the technical solutions of early strength setting and steel fiber anti-cracking, but fails to effectively solve the problems of early segregation of concrete and insufficient crack resistance in the middle and late stages under disturbance conditions; Chinese Patent 202111052288.3 provides an early high disturbance-resistant bridge splicing concrete, which mainly introduces materials such as sulphoaluminate cement, polymer composite chopped fibers, basalt fibers and early strength agents to improve the disturbance-resistant effect of concrete, but there is no targeted solution for the easy sinking and segregation of early aggregates in concrete.
[0005] Therefore, under the condition that traffic cannot be interrupted and the structural disturbance caused by traffic load cannot be reduced, the preparation of anti-disturbance concrete needs to focus on and solve two key technical problems: one is that the aggregate is easy to segregate when the concrete is flowing, and the other is that it is easy to crack and reduce strength during the setting and hardening process. Only by comprehensively optimizing the design of the components of anti-disturbance concrete and forming a synergistic combination can the anti-disturbance and anti-cracking performance of concrete reach the best state. Summary of the invention
[0006] In view of the deficiencies of the above prior art, one of the purposes of the present invention is to provide an anti-disturbance and anti-cracking concrete, which solves the problem of easy segregation of fresh concrete aggregate under vibration disturbance conditions by using modified aggregate suspension and cement-based slurry thickening, and at the same time uses modified iron tailings sintered aggregate to cross-lap and block the fibers, so that the fibers can still be crisscrossed in the cement slurry under vibration conditions, effectively achieving the vibration reduction, toughening and anti-cracking effect of the fibers. Under the synergistic effect of various components, the problems of poor anti-disturbance performance, easy segregation, cracking and reduced strength of fresh and coagulated hardened concrete under vibration environment conditions are solved.
[0007] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0008] A disturbance-resistant and crack-resistant concrete comprises the following components in parts by weight: 400-520 parts of cementitious material, 710-800 parts of fine aggregate, 1030-1080 parts of modified iron tailings sintered aggregate, 0.6-1.2 parts of sodium hydroxymethyl cellulose, 1.5-3 parts of fiber, 5-8 parts of water reducer, and 140-155 parts of water;
[0009] The preparation method of the modified iron tailings sintered aggregate comprises the following steps:
[0010] The iron tailings, bauxite tailings and limestone are mixed and then granulated, polyvinyl alcohol aqueous solution is added during the granulation process, and the iron tailings sintered aggregate is obtained after drying.
[0011] The iron tailings sintered aggregate is soaked in a mixed solution of gelatin and glutaraldehyde, short-cut fibers are added, and vacuum is drawn after ultrasonic dispersion, with a vacuum pressure of -0.1 to -0.2 MPa. The modified iron tailings sintered aggregate is obtained after being taken out and dried.
[0012] The density of common clay or shell rock sintered aggregate is generally 800-1400kg / m 3 The aggregate of the concrete prepared by it is relatively easy to float under vibration conditions, while the density of conventional limestone, granite and basalt crushed stone aggregates is generally 2400-2800kg / m 3 The aggregate of the concrete prepared by the method is easy to sink under vibration conditions, resulting in concrete segregation. The present invention uses iron tailings as the main component material, combined with bauxite and limestone, and the density of the aggregate prepared by sintering is 1800-2000kg / m 3 , it can be achieved that under vibration conditions, the aggregate is neither easy to float nor easy to sink in the cement slurry. The density of iron tailings is relatively large, and it is rich in iron oxides, silicates, etc. Bauxite is rich in SiO2, Al2O3, etc. These components can form a molten phase at high temperature, which helps to bond between particles, form a denser sintered aggregate structure, and ensure the density of sintered aggregate. Limestone acts as a flux and pore-forming agent to improve the sintering strength of aggregates and increase porosity, while also providing calcium. Polyvinyl alcohol solution can form a bonding film during granulation and sintering, improve the adhesion between particles, and polyvinyl alcohol will decompose at high temperature during sintering, releasing gas, which promotes the formation of pores on the surface of sintered aggregates. The pores of the modified iron tailings sintered aggregate help absorb impact or vibration energy during the coagulation and hardening of concrete, forming a certain buffering effect, thereby reducing the impact of vibration conditions on the structure.
[0013] The toughness of chopped fibers can improve the vibration resistance of concrete. Modified iron tailings sintered aggregate is added to the gelatin aqueous solution and chopped fiber mixture. Through ultrasonic vibration, the fibers in the solution can be evenly distributed and the contact with the pore wall of the sintered aggregate can be enhanced. At this time, vacuum (negative pressure) is applied, the gas in the pores of the aggregate is extracted, and the liquid (solution containing fibers) is pushed by the negative pressure and enters the pores of the aggregate. At the same time, the chopped fibers are "pulled into" the pores. The gelatin solution has strong hydrophilicity and adhesion, and can be hydrophilic with the chopped fibers, adhere to the fibers and perform viscous filling of the sintered aggregate. Glutaraldehyde is a cross-linking agent, and its aldehyde group can react with the amino group of the gelatin molecule to form an imine bond, connecting the gelatin molecules. Under the promotion of heating, the gelatin forms a more solid three-dimensional network structure, fixing the chopped fibers in the pores of the iron tailings sintered aggregate, and realizing that a large number of relatively upright chopped fibers are embedded in the pores on the surface of the iron tailings sintered aggregate. Under vibration disturbance conditions, the multiple strands of fibers on the surface of the modified iron tailings sintered aggregate in the fresh concrete form friction and support with the cement paste near the aggregate, thus helping to suspend the aggregate; at the same time, the multiple strands of chopped fibers on the surface of the modified iron tailings sintered aggregate can form cross-lapping barriers to the fibers in the concrete, so that under continuous high-frequency vibration conditions, the fibers can still maintain a criss-cross distribution, effectively achieving the effect of vibration reduction, toughening and crack resistance. In addition, the toughness of the chopped fibers adhered to the three-dimensional mesh structure of gelatin is improved, and they can better absorb during the coagulation and hardening process of concrete, thereby improving the impact resistance, strength and crack resistance of concrete.
[0014] Sodium hydroxymethyl cellulose is a highly water-soluble polymer that can form polymer chains in cement paste. Through the mutual entanglement of molecules, a network structure is formed, which increases the consistency and viscosity of concrete paste, making it difficult for water and paste to float up. It synergistically modifies the suspension properties of iron tailings sintered aggregates, so that cement paste and aggregates can be more evenly distributed in concrete under vibration conditions, avoiding stratification and segregation of cement and aggregates. At the same time, sodium hydroxymethyl cellulose molecules contain a large number of hydroxyl and ether groups. These hydrophilic groups can form stable hydrogen bonds with water molecules, enhance the water retention capacity of concrete, and ensure that cement particles are fully hydrated by retaining water and delaying water growth, thereby improving concrete strength and avoiding shrinkage cracks.
[0015] Preferably, the iron tailings sintered aggregate has a particle size of 5-20 mm and a density of 1800-2000 kg / m 3 , water absorption rate is less than 10%.
[0016] Preferably, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 6% to 10%.
[0017] Preferably, the mass ratio of the iron ore tailings, bauxite tailings and limestone is (80-85):(8-15):(5-7).
[0018] Preferably, the sintering temperature is 1140-1180° C., and the sintering time is 20-50 min.
[0019] Preferably, in the mixed solution of gelatin and glutaraldehyde, the concentration of gelatin is 10wt%~15wt%, and the concentration of glutaraldehyde is 0.05wt%~0.1wt%.
[0020] Preferably, the chopped fibers are aramid chopped fibers with a length of 3 to 5 mm.
[0021] Preferably, the mass of the chopped fibers is 0.8% to 1.0% of the mass of the iron ore tailings sintered aggregate.
[0022] Preferably, the fiber is a rubber latex modified fiber, and the preparation method of the rubber latex modified fiber is as follows: soak the polyvinyl alcohol fiber in a silane coupling agent solution, take it out and place it in a natural rubber composite carbon nanotube emulsion, take it out and dry it after ultrasonic dispersion; then soak it in a hydrogen peroxide solution and stir it evenly, take it out and rinse it with clean water, and dry it to obtain the rubber latex modified fiber.
[0023] Polyvinyl alcohol fiber has good mechanical strength, adhesion and high flexibility. After being treated with deionized water and silane coupling agent, the bonding between polyvinyl alcohol fiber and natural rubber can be effectively improved. Natural rubber has excellent elasticity and vibration absorption and vibration reduction effects. The fiber wrapped in it can absorb vibration energy when added to concrete, forming a flexible "spring" effect, effectively weakening the impact of vibration environment conditions on concrete. Carbon nanotubes can further improve the elasticity and vibration reduction ability of rubber. Carbon nanotubes can form raised particles on the surface of natural rubber latex wrapped on the fiber surface. Not only can the nanofiber characteristics of carbon nanotubes be utilized, but the vibration energy can be more effectively dispersed in all directions, and the bonding strength between the modified fiber and concrete can be effectively increased. Oxidation treatment of the fiber wrapped with natural rubber using hydrogen peroxide can produce a tiny oxide layer on its surface, increase the polarity and roughness of its surface, and improve the bonding between the fiber and concrete. Carbon nanotubes and hydrogen peroxide treatment effectively enhance the bonding ability between rubber latex modified fibers and cement paste, and synergistically modify the iron tailings sintered aggregate (the multiple strands of aramid chopped fibers on the surface of the aggregate block the cross-overlapping of the rubber latex modified fibers). Under dynamic conditions of continuous high-frequency vibration, the rubber latex modified fibers can still maintain a criss-cross distribution and a relatively consistent distribution in difficult directions. The fibers effectively disperse stress and absorb vibration energy, fully improving the mechanical properties, toughness and probability of cracks in concrete under vibration conditions.
[0024] In the above technical solution, the natural rubber composite carbon nanotube emulsion is formed by mixing natural rubber emulsion and carbon nanotubes in a mass ratio of 100:10 to 100:15, and the solid content of the natural rubber emulsion is 60% to 70%.
[0025] In the above technical solution, the length of the carbon nanotubes is 40-60 μm, and the specific surface area is greater than 100 m 2 / g.
[0026] Another object of the present invention is to provide a method for preparing the anti-disturbance and anti-cracking concrete, comprising the following steps:
[0027] M1. Weigh each component by weight;
[0028] M2. The cementitious material, fine aggregate, sodium hydroxymethyl cellulose, 2 / 3 of the water reducer and 2 / 3 of the water are mixed evenly, and then the modified iron tailings sintered aggregate is added and mixed evenly, and then the fiber, 1 / 3 of the water reducer and 1 / 3 of the water are added and mixed evenly to obtain a concrete slurry.
[0029] Compared with the prior art, the present invention is beneficial in that:
[0030] (1) The density of the iron ore tailings sintered aggregate of the present invention is 1800-2000 kg / m 3 Under vibration conditions, aggregates are neither easy to float nor easy to sink in cement paste. The pores of sintered iron tailings aggregates can absorb impact vibration energy. By embedding multiple strands of chopped fibers relatively upright into the porous structure on the surface of sintered aggregates, multiple strands of fibers on the surface of modified sintered iron tailings aggregates in fresh concrete under vibration disturbance conditions can form friction and support with the cement paste near the aggregates, thereby helping to suspend the aggregates. At the same time, multiple strands of chopped fibers form cross-overlapping barriers to the fibers in the concrete, preventing the fibers from becoming distributed in a relatively consistent direction under vibration conditions. In addition, the thickening and water-retention effects of sodium hydroxymethyl cellulose are synergistic, so that aggregates are evenly distributed in the cement paste of fresh concrete under vibration conditions, avoiding stratification and segregation of cement and aggregates, while improving concrete strength and shrinkage and crack resistance.
[0031] (2) The present invention uses natural rubber to wrap polyvinyl alcohol fibers to form a flexible "spring" effect, which effectively weakens the impact of vibration environment conditions on concrete. Carbon nanotubes further enhance the elasticity and vibration reduction capabilities of rubber, and disperse vibration energy in multiple directions. Carbon nanotubes and hydrogen peroxide strengthen the bonding ability between rubber latex modified fibers and cement paste, and cooperate with the cross-overlapping barrier of short-cut fibers on the surface of modified iron tailings sintered aggregates to achieve continuous high-frequency vibration dynamic conditions. The rubber latex modified fibers can still maintain a criss-cross distribution. The fibers can effectively disperse stress and absorb vibration energy, effectively enhancing the density and strength of concrete, and reducing the probability of cracks and delaying the development of cracks. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the following embodiments and comparative examples, cement is ordinary Portland cement P•O 52.5; sand can be natural river sand and / or machine-made sand. When it is a mixture of natural river sand and machine-made sand, the mass ratio of machine-made sand to natural river sand is (2-3):(7-8), the fineness modulus of natural sand is 2.8-3.2, the fineness modulus of machine-made sand is 2.7-3.0, and the stone powder content is less than 10%; the water reducer is a polycarboxylate water reducer, the water reduction rate is 35%, and the solid content is 37%; the hydroxypropyl content in sodium hydroxymethyl cellulose is 7-10%, and the methoxy content is 20-24%.
[0034] The particle size of iron tailings is 2.36mm or less, with SiO2 content >65% and Al2O3 content >10%. The length of aramid short-cut fibers is 3-5mm, the diameter is 10-20μm, and the elastic modulus is 120-150GPa. The length of carbon nanotubes is 40-60μm, and the specific surface area is >100m 2 / g.
[0035] Example 1
[0036] This embodiment provides an anti-disturbance and anti-cracking concrete, comprising the following components in parts by weight: 380 parts of cement, 70 parts of fly ash, 30 parts of slag powder, 8 parts of silica fume, 800 parts of sand, 1080 parts of modified iron tailings sintered aggregate, 1.2 parts of sodium hydroxymethyl cellulose, 3 parts of polyvinyl alcohol fiber, 8 parts of water reducer, and 140 parts of water;
[0037] The preparation method of modified iron tailings sintered aggregate is as follows:
[0038] S1. Weigh 85 parts of iron tailings, 8 parts of bauxite tailings and 7 parts of limestone by weight, add them into a ball mill with a rotation speed of 300r / min and blend for 60min, use a granulator to maintain the rotation speed of 20r / min, add an appropriate amount of polyvinyl alcohol aqueous solution for granulation, the concentration of the polyvinyl alcohol aqueous solution is 6wt%, take out and dry, place in a sintering furnace at a temperature of 1140°C for 30min, and sieve to obtain iron tailings sintered aggregate with a diameter of 5~20mm; after testing, the apparent density of the iron tailings aggregate prepared in this embodiment is 1950kg / m 3 .
[0039] S2. The iron tailings sintered aggregate obtained in step S1 is soaked in a mixed aqueous solution of gelatin and glutaraldehyde for 20 minutes, wherein the concentration of gelatin in the mixed aqueous solution is 15wt%, and the concentration of glutaraldehyde is 0.1%; then, 0.9% by weight of aramid chopped fibers of the iron tailings sintered aggregate are added, and ultrasonic vibration is performed for 10 minutes. At the same time, vacuum is drawn and a vacuum pressure of -0.1MPa is maintained for 20 minutes. The aggregate is taken out and placed in an oven at 60°C for curing for 40 minutes. The aggregate is taken out and cooled to obtain the modified iron tailings sintered aggregate.
[0040] The method for preparing the anti-disturbance and anti-cracking concrete of this embodiment comprises the following steps:
[0041] M1. Weigh each component by weight;
[0042] M2. Mix cement, fly ash, slag powder, silica fume, sand, sodium hydroxymethyl cellulose, 2 / 3 water reducer and 2 / 3 water for 60-80 seconds until uniform. Then add modified iron tailings sintered aggregate and mix for 40-60 seconds. Then add fiber, 1 / 3 water reducer and 1 / 3 water and mix well to obtain anti-disturbance and anti-cracking concrete slurry.
[0043] In the steps, 2 / 3 of the water reducer refers to 2 / 3 of the total amount of the water reducer, and 1 / 3 of the water reducer refers to 1 / 3 of the total amount of the water reducer; 2 / 3 of the water refers to 2 / 3 of the total amount of the water, and 1 / 3 of the water refers to 1 / 3 of the total amount of the water.
[0044] Example 2
[0045] The anti-disturbance and anti-cracking concrete of this embodiment is basically the same as that of Embodiment 1, except that the anti-disturbance and anti-cracking concrete of this embodiment includes the following components in parts by weight: 320 parts of cement, 50 parts of fly ash, 50 parts of slag powder, 12 parts of silica fume, 710 parts of sand, 1030 parts of modified iron tailings sintered aggregate, 0.6 parts of sodium hydroxymethyl cellulose, 1.5 parts of polyvinyl alcohol fiber, 5 parts of water reducer, and 155 parts of water;
[0046] The preparation method of modified iron tailings sintered aggregate is as follows:
[0047] S1. Weigh 80 parts of iron tailings, 15 parts of bauxite tailings and 5 parts of limestone by weight, add them into a ball mill with a rotation speed of 400r / min and blend for 40min, use a granulator to maintain the rotation speed of 30r / min, add an appropriate amount of polyvinyl alcohol aqueous solution for granulation, the concentration of the polyvinyl alcohol aqueous solution is 10wt%, take out and dry, place in a sintering furnace at a temperature of 1180°C for 20min, and sieve to obtain iron tailings sintered aggregate with a diameter of 5~20mm; after testing, the density of the iron tailings aggregate prepared in this embodiment is 1850kg / m 3 .
[0048] S2. The iron tailings sintered aggregate obtained in step S1 is soaked in a mixed aqueous solution of gelatin and glutaraldehyde for 30 minutes, wherein the concentration of gelatin in the mixed aqueous solution is 10wt%, and the concentration of glutaraldehyde is 0.05%; then, aramid chopped fibers accounting for 1.0% of the mass of the iron tailings sintered aggregate are added, and ultrasonic vibration is performed for 20 minutes. At the same time, vacuum is drawn and a vacuum pressure of -0.2MPa is maintained for 10 minutes. The aggregate is taken out and placed in an oven at 70°C for curing for 30 minutes. The aggregate is taken out and cooled to obtain the modified iron tailings sintered aggregate.
[0049] Example 3
[0050] The anti-disturbance and anti-cracking concrete of this embodiment is basically the same as that of embodiment 1, except that the fiber used in this embodiment is rubber latex modified fiber, and the preparation method of rubber latex modified fiber is as follows: the polyvinyl alcohol fiber is washed and dried with deionized water, and then immersed in a 3-aminopropyl triethoxysilane coupling agent solution for 20 minutes, and then taken out and placed in a natural rubber composite carbon nanotube emulsion, in which the solid content of natural rubber emulsion in the natural rubber composite carbon nanotube emulsion is 60%, and the mass of carbon nanotubes is 10% of the natural rubber emulsion, and then ultrasonically dispersed for 15 minutes and then taken out and dried at 60°C. Then, it is immersed in a 25wt% hydrogen peroxide solution and stirred at a low speed for 30 minutes, and then taken out and rinsed with clean water and dried to obtain rubber latex modified fiber.
[0051] Example 4
[0052] The anti-disturbance and anti-cracking concrete of this embodiment is basically the same as that of embodiment 1, except that the fiber used in this embodiment is rubber latex modified fiber, and the preparation method of rubber latex modified fiber is as follows: the polyvinyl alcohol fiber is washed and dried with deionized water, and then immersed in a 3-aminopropyl triethoxysilane coupling agent solution for 30 minutes, and then taken out and placed in a natural rubber composite carbon nanotube emulsion, in which the solid content of natural rubber emulsion in the natural rubber composite carbon nanotube emulsion is 50%, and the mass of carbon nanotubes is 15% of the natural rubber emulsion, and then ultrasonically dispersed for 30 minutes and then taken out and dried at 80°C. Then, it is immersed in a 30wt% hydrogen peroxide solution and stirred at a low speed for 20 minutes, and then taken out and rinsed with clean water and dried to obtain rubber latex modified fiber.
[0053] Example 5
[0054] The anti-disturbance and anti-cracking concrete of this embodiment is basically the same as that of Embodiment 1, with the only difference being that the fiber used in this embodiment is rubber latex-modified fiber, and the preparation method of the rubber latex-modified fiber is as follows: the polyvinyl alcohol fiber is washed and dried with deionized water, and then immersed in a 3-aminopropyltriethoxysilane coupling agent solution for 20 minutes, taken out and placed in a natural rubber latex with a solid content of 60%, and then ultrasonically dispersed for 15 minutes and fished out, rinsed with clean water, and dried to obtain the rubber latex-modified fiber.
[0055] Comparative Example 1
[0056] The concrete of Comparative Example 1 is basically the same as that of Example 1, except that the preparation method of the modified iron tailings sintered aggregate in this comparative example is as follows: 85 parts of iron tailings, 8 parts of bauxite tailings and 7 parts of limestone are weighed by weight, added to a ball mill at a rotation speed of 300 r / min and blended for 60 minutes, and a granulator is used to add an appropriate amount of polyvinyl alcohol aqueous solution for granulation while maintaining a rotation speed of 20 r / min. The concentration of the polyvinyl alcohol aqueous solution is 6wt%. After taking out and drying, it is placed in a sintering furnace at a temperature of 1140°C and sintered for 30 minutes. After sieving, a modified iron tailings sintered aggregate with a diameter of 5~20 mm is obtained.
[0057] That is, compared with Example 1, step S2 is omitted in this comparative example.
[0058] Test example
[0059] The working performance, mechanical properties and crack resistance of the concrete of each embodiment and comparative example under vibration conditions were tested. The test results are shown in Table 1.
[0060] The test is based on the provisions of the Highway Engineering Technical Standard (JTG B01-2014): the annual average daily design traffic volume of expressways and first-class highways is more than 15,000 passenger cars. Combined with the fact that two-wheeled passenger cars generate two vibrations every time they pass through the structure, it is calculated that the annual average daily vibration frequency of the eight-lane first-class highway structure is more than 2.78Hz. Considering the actual traffic conditions of half-width traffic, 5 Hz is selected as the simulation object, that is, 18,000 times / h. The specific disturbance simulation working condition is set as follows: a 50 Hz horizontal electric vibration table is used to provide disturbance, with an amplitude of 2 mm and 18,000 vibrations per hour, that is, the vibration table is turned on, each vibration is 99 s, and each rest is 15 minutes. The vibration cycle is 4 times within an hour, and the total duration of the vibration environment condition is 24 hours.
[0061] According to the provisions of GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the working performance of the freshly mixed concrete of the examples and comparative examples was tested, including fluidity and segregation, wherein fluidity was characterized by slump and segregation was qualitatively characterized by the state of concrete; the mechanical properties of concrete were tested according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete"; and the crack resistance of concrete was tested according to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The crack resistance of concrete was determined by the "cracking plate test", and the test results were expressed as the total cracking area per unit area calculated, and the smaller the value, the better the crack resistance.
[0062] Table 1 Concrete performance test results
[0063] From the test results in Table 1, it can be seen that in terms of working performance, the slump of the concrete of Examples 1-5 is generally 170-180 mm. Whether ordinary polyvinyl alcohol fiber or rubber latex modified fiber is used in the concrete, the concrete has relatively good flowability and workability under the continuous vibration condition. During the test, it was observed that the cohesiveness and water retention of the concrete were generally good, no aggregate floated or sank in the concrete, and no segregation of the concrete occurred. Compared with Example 1, step S2 was omitted when preparing the modified iron tailings sintered aggregate in Comparative Example 1. Under the vibration condition, although the flowability of the concrete was slightly improved, a slight segregation phenomenon occurred, which shows that the embedded design of the chopped fiber on the surface of the sintered aggregate can effectively realize the friction and support force formed between the modified iron tailings sintered aggregate and the cement slurry, realize the suspension of the aggregate in the cement slurry, and avoid the segregation of the concrete.
[0064] In terms of mechanical properties and crack resistance, the 28d compressive strength and total crack area per unit area of Examples 1-2 using ordinary polyvinyl alcohol fibers are 52.2-52.4 MPa and 121-124 mm 2 / m 2 The mechanical properties are good, and the flat plate has almost no cracks visible to the naked eye, and the crack resistance is excellent. Compared with Example 1, the concrete of Example 3-Example 4 uses rubber latex modified fiber, and the 28d compressive strength and total crack area per unit area are 55.5~55.8MPa and 82~86mm, respectively. 2 / m 2 There are almost no cracks visible on the surface of the flat plate, and the mechanical properties and crack resistance of the concrete are excellent. This shows that the use of natural rubber composite carbon nanotube emulsion and hydrogen peroxide solution to modify polyvinyl alcohol fiber can effectively weaken the impact of vibration environment conditions on concrete, and further improve the mechanical properties and crack resistance of concrete.
[0065] The 28d compressive strength and total crack area per unit area of Example 5 were 53.7 MPa and 99 mm 2 / m 2 By comparing Example 3 and Example 5, it can be found that carbon nanotubes can disperse vibration energy in multiple directions, further improving the elasticity and vibration reduction ability of rubber. At the same time, carbon nanotubes and hydrogen peroxide can strengthen the bonding ability between rubber latex modified fiber and cement paste, improve the compactness of concrete and effectively exert the crack resistance of fiber. Compared with Example 1, the 28d compressive strength and total crack area per unit area of Comparative Example 1 are 49.4MPa and 145mm, respectively. 2 / m 2 This indicates that the chopped fibers on the surface of the modified iron tailings sintered aggregate can form a cross-overlap barrier with the fibers, so that under the dynamic working condition of continuous high-frequency vibration, the fibers can still maintain a criss-cross distribution. The fibers can disperse stress in multiple directions, effectively enhance the density of concrete, and reduce the probability of cracks and delay the development of cracks.
[0066] In addition, the inventors also tested the performance of concrete under vibration conditions. By comparing the concrete test data before and after the vibration conditions, it was found that the various performance parameters of the concrete were basically the same, indicating that the vibration disturbance conditions would not have a deteriorating effect on the performance of the concrete of the present invention.
[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A disturbance-resistant and crack-resistant concrete, characterized in that: The invention comprises the following components in parts by weight: 400-520 parts of cementitious material, 710-800 parts of fine aggregate, 1030-1080 parts of modified iron tailings sintered aggregate, 0.6-1.2 parts of sodium hydroxymethyl cellulose, 1.5-3 parts of fiber, 5-8 parts of water reducer and 140-155 parts of water; The preparation method of the modified iron tailings sintered aggregate comprises the following steps: The iron tailings, bauxite tailings and limestone are mixed and then granulated, polyvinyl alcohol aqueous solution is added during the granulation process, and the iron tailings sintered aggregate is obtained after drying. The iron tailings sintered aggregate is soaked in a mixed solution of gelatin and glutaraldehyde, short-cut fibers are added, and vacuum is drawn after ultrasonic dispersion, with a vacuum pressure of -0.1 to -0.2 MPa. The modified iron tailings sintered aggregate is obtained after being taken out and dried.
2. The anti-disturbance and anti-cracking concrete according to claim 1, characterized in that: The mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 6% to 10%.
3. The anti-disturbance and anti-cracking concrete according to claim 1, characterized in that: The mass ratio of the iron tailings, bauxite tailings and limestone is (80-85):(8-15):(5-7).
4. The anti-disturbance and anti-cracking concrete according to claim 1, characterized in that: The sintering temperature is 1140-1180° C., and the sintering time is 20-50 minutes.
5. The anti-disturbance and anti-cracking concrete according to claim 1, characterized in that: In the mixed solution of gelatin and glutaraldehyde, the concentration of gelatin is 10wt%-15wt%, and the concentration of glutaraldehyde is 0.05wt%-0.1wt%.
6. The anti-disturbance and anti-cracking concrete according to claim 1, characterized in that: The chopped fibers are aramid chopped fibers with a length of 3 to 5 mm.
7. The anti-disturbance and anti-cracking concrete according to claim 1, characterized in that: The fiber is a rubber latex modified fiber, and the preparation method of the rubber latex modified fiber is as follows: the polyvinyl alcohol fiber is immersed in a silane coupling agent solution, taken out and placed in a natural rubber composite carbon nanotube emulsion, and then ultrasonically dispersed and taken out and dried; then immersed in a hydrogen peroxide solution and stirred evenly, taken out and rinsed with clean water, and dried to obtain the rubber latex modified fiber.
8. The anti-disturbance and anti-cracking concrete according to claim 7, characterized in that: The natural rubber composite carbon nanotube emulsion is prepared by mixing natural rubber emulsion and carbon nanotubes in a mass ratio of 100:10 to 100:15, and the solid content of the natural rubber emulsion is 60% to 70%.
9. The anti-disturbance and anti-cracking concrete according to claim 8, characterized in that: The carbon nanotubes have a length of 40-60 μm and a specific surface area of more than 100 m 2 / g.
10. The method for preparing the disturbance-resistant and crack-resistant concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: M1. Weigh each component by weight; M2. The cementitious material, fine aggregate, sodium hydroxymethyl cellulose, 2 / 3 of the water reducer and 2 / 3 of the water are mixed evenly, and then the modified iron tailings sintered aggregate is added and mixed evenly, and then the fiber, 1 / 3 of the water reducer and 1 / 3 of the water are added and mixed evenly to obtain a concrete slurry.
Citation Information
Patent Citations
Early-stage high-disturbance-resistance bridge splicing concrete
CN113735535A
Anti-disturbance concrete and preparation method thereof
CN117756485A